Multispectral method for skin imaging: development and validation - Shi, Tianchen; DiMarzio, Charles A (Applied optics (2004), 2007)
A visible wide field multispectral system for comprehensive imaging of skin chromophores and blood vessels has been implemented, and an inhomogeneous Monte Carlo model of photon migration with randomly distributed blood vessels embedded in dermis has been developed. Predetermined nonlinear transforms have been obtained to address the nonlinear interdependent relationship among diffusive reflectance spectra, skin physiology properties, and geometry. For validation, in addition to real skin experiments and phantoms experiments, two alternative methods for blood vessel imaging have been used on the same set of subjects to compensate for the lack of ground truth for skin subsurface imaging.